JURIDICIAL REVIEW OF GOVERNMENT PROCUREMENT OF GOODS AND SERVICES BASED ON PRESIDENTIAL REGULATION 12 2021 IN CONJUNCTION OF PRESIDENTIAL REGULATION 16 2018 - Ahmaddien, Iskandar (Transpublika Publisher, 2021)
There are a variety of issues that arise in the procurement of government goods and services, ranging from effectiveness and efficiency to the misuse of funds allocated to the procurement of goods and services by the government. Following the numerous issues that arose, the government took efforts to change its policies on goods and services as a result of the various issues that arose. Policy modifications are established by issuing a Presidential Regulation (Perpres) governing the procurement of new goods and services, particularly Presidential Regulation Number 12 of 2021 to reinforce Presidential Regulation Number 16 of 2018. Qualitative methods were used in conjunction with document studies in this study. In this study, secondary data in the form of primary legal materials, in this case Presidential Regulation No. 12 of 2021 concerning the procurement of government goods and services, was used to support the findings of existing scientific research and various related literature. The primary legal materials used in this study were Presidential Regulation No. 12 of 2021 concerning the procurement of government goods and services, which was supported by the findings of existing scientific research and various related literature. The results of this study are the governance of government procurement of goods/services in Presidential Regulation Number 12 of 2021 as a refinement of Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services (hereinafter referred to as Perpres 16/2018) which was promulgated in March 2018. This regulation is intended to accelerate and simplify the process, as well as provide value for money and also easy to manage and supervise.